Fostering motivation in ESL collaborative online writing through google docs - Sharifahtun Naim, Shahidan; Zuraina, Ali; Tilwani, Shouket Ahmad (Sciedu Press, 2022)
This paper presents the English as A Second Language (ESL) learners’ motivation for using Google Docs to write collaboratively. The study includes learners’ motivations for using Google Docs in writing regarding interaction with classmates and a lecturer. It employed a descriptive research design in collecting the data for the current study. Eighty (80) diploma students were included in the study to identify their experiences of using the platform in two critical variables – collaboration and motivation. Findings show that Google Docs is beneficial to creating a supportive and motivating learning environment for them, along with collaboration and interaction with their peers and the lecturer. This study has demonstrated that integrating Google Docs in writing can encourage learners’ motivation and, therefore, is significant to the social and psychological well-being to promote a practical approach to writing collaboratively among L2 learners. This is due to growing up in the digital age that requires learners to be prepared to use various digital tools, including Google Docs. Last but not least, the study suggests that different methodologies can be employed to investigate further learners’ motivation as they collaborate with their peers and teacher in writing using Google Docs.